2019
DOI: 10.1186/s13104-019-4561-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with hepatitis B virus infection among pregnant women attending antenatal clinic at Felegehiwot referral hospital, Northwest Ethiopia, 2018: an institution based cross sectional study

Abstract: Objective This study aimed to determine the magnitude of serum HBsAg and the risk factors for hepatitis B virus infection among pregnant women in Bahir Dar. An institution based cross sectional study was implemented from February 1 to May 1, 2018 among 338 pregnant women attending antenatal care clinic at Felegehiwot referral hospital, Bahir Dar, 2018. Systematic random sampling technique was implemented. Blood sample was taken from 338 study participants and serum was tested for hepatitis B surfa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
11
22
3
Order By: Relevance
“…. Twenty-three of the studies included in the final analysis were cross-sectional [11,14,23,24,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. The studies used health facilitybased HBV infection data among pregnant women which were collected from 2002 to 2018 in the respective health institutions.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…. Twenty-three of the studies included in the final analysis were cross-sectional [11,14,23,24,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. The studies used health facilitybased HBV infection data among pregnant women which were collected from 2002 to 2018 in the respective health institutions.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The studies used health facilitybased HBV infection data among pregnant women which were collected from 2002 to 2018 in the respective health institutions. Seven articles were conducted at the Southern Nations, Nationalities, and Peoples' Region (SNNPR) [11,14,29,31,35,39,47], five in Amhara region [23,24,30,32,36], five in Oromia region [33,37,38,41,44], and three in Addis Ababa [34,41,42], whereas one in Tigray [46], Harar [43], and Gambella [45]. The sample size of included studies ranges from a minimum of 165 pregnant women in SNNPR [39] to 580 in Oromia [38].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a retrospective study in Cameroon found a significant relationship between occupation [10] and age [6,11], and HBV infection among pregnant women [11]. In Nigeria, Anaedobe, Fowotade [12], revealed that pregnant women with multiple sexual partners [6,10,[13][14][15] and those who experienced early sexual debut were more likely to be infected with HBV. Other risk factors include marital status, history of abortion, blood transfusion and surgery, family history of HBV infection, and alcohol intake [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, Anaedobe, Fowotade [12], revealed that pregnant women with multiple sexual partners [6,10,[13][14][15] and those who experienced early sexual debut were more likely to be infected with HBV. Other risk factors include marital status, history of abortion, blood transfusion and surgery, family history of HBV infection, and alcohol intake [10][11][12][13][14][15][16]. However, other studies in sub-Saharan Africa including Ghana, found no significant association between participants' characteristics and HBV positivity [8,9].…”
Section: Introductionmentioning
confidence: 99%